P-glycoprotein (Mdr1a/1b) and breast cancer resistance protein (Bcrp) decrease the uptake of hydrophobic alkyl triphenylphosphonium cations by the brain - Porteous, Carolyn M.; Menon, David K.; Aigbirhio, Franklin I.; Smith, Robin A.J.; Murphy, Michael P. (Biochimica et biophysica acta, 2013)
Mitochondrial dysfunction contributes to degenerative neurological disorders, consequently there is a need for mitochondria-targeted therapies that are effective within the brain. One approach to deliver pharmacophores is by conjugation to the lipophilic triphenylphosphonium (TPP) cation that accumulates in mitochondria driven by the membrane potential. While this approach has delivered TPP-conjugated compounds to the brain, the amounts taken up are lower than by other organs. To discover why uptake of hydrophobic TPP compounds by the brain is relatively poor, we assessed the role of the P-glycoprotein (Mdr1a/b) and breast cancer resistance protein (Bcrp) ATP binding cassette (ABC) transporters, which drive the efflux of lipophilic compounds from the brain thereby restricting the uptake of lipophilic drugs. We used a triple transgenic mouse model lacking two isoforms of P-glycoprotein (Mdr1a/1b) and the Bcrp. There was a significant increase in the uptake into the brain of two hydrophobic TPP compounds, MitoQ and MitoF, in the triple transgenics following intra venous (IV) administration compared to control mice. Greater amounts of the hydrophobic TPP compounds were also retained in the liver of transgenic mice compared to controls. The uptake into the heart, white fat, muscle and kidneys was comparable between the transgenic mice and controls. Efflux of hydrophobic TPP compounds by ABC transporters contributes to their lowered uptake into the brain and liver. These findings suggest that strategies to bypass ABC transporters in the BBB will enhance delivery of mitochondria-targeted antioxidants, probes and pharmacophores to the brain. ► Brain accumulation of triphenylphosphonium cations is decreased by ABC transporters. ► ABC-transporter inactivation increases brain uptake of triphenylphosphonium cations. ► Bypassing ABC transporters may increase the effectiveness of mitochondrial therapies.